Is the dynamics of dissipative lorentzian channels non markovian? (2013)
We consider the dissipative dynamics of an exciton in a Lorentzian reservoir, relevant in the description of some photosynthetic complexes. Although this dynamics have been frequently described as non-Markovian, we show that this characterization may be misleading. We describe an approach within which it is possible to decide if thisdynamics is or not Markovian. We apply this approach to the Lorentzian reservoir.